COVID-19 with cystic features on computed tomography: A case report. Issue 18 (May 2020) - Liu, Kefu; Zeng, Yuanying; Xie, Ping; Ye, Xun; Xu, Guidong; Liu, Jian; Wang, Hao; Qian, Jinxian
Abstract: Rationale: The cystic features of the novel coronavirus disease 2019 (COVID-19) found on computed tomography (CT) have not yet been reported in the published literature. We report the cystic chest CT findings of 2 patients confirmed to have COVID-19-related pneumonia. Patient concerns: A 38-year-old man and a 35-year-old man diagnosed with severe COVID-19 pneumonia were admitted to the intensive care unit. Diagnoses: Chest CT findings showed multiple cysts in ground-glass opacities (bilaterally) with/without pneumothorax. The cysts had a smooth inner wall. Interventions: The patients continued to be given oxygen by mask and received antitussive, phlegm-dispelling treatment. Outcomes: At follow up, there was a reduction in the number of multiple cystic lesions on CT. To date, 1 patient was discharged from hospital, while the other had been transferred to the rehabilitation department. Lessons: COVID-19 may independently result in pulmonary cyst formation and pneumothorax; the application of a ventilator may be another causative factor.